Assessing Inflation Rate Forecast Performance: A Setar Model Approach for Sustainable Economic Growth (British Journal of Multidisciplinary and Advanced Studies, 2024)
The relationship between inflation rates and the sustainability of a country's GDP is a crucial aspect of economic development, with profound implications for sustainable growth and development. This research investigates the complex relationship that exists between inflation rates and the sustainable growth of Nigeria's GDP. It also evaluates the prediction accuracy of the Self-Exciting Threshold Autoregressive (SETAR) model. Using Central Bank of Nigeria data from January 2013 to March 2021, a two-regime nonlinear SETAR model is used to capture the nonlinear dynamics that are present in inflation. The study concludes that the SETAR (2;14,13) model is a better predictor of inflation rates after thorough evaluation using metrics like Mean Absolute Error (MAE) and Root Mean Squared Error (RMSE). The study has substantial implications for sustainable development because it offers analysts, investors, and policymakers useful information about how inflation may affect GDP sustainability. This study provides stakeholders with the necessary tools to formulate effective policies aimed at mitigating the negative effects of inflation on sustainable economic growth (SDG 8), thereby fostering long-term development and prosperity. Specifically, the SETAR (2;14,13) model is one of the accurate forecasting models that this study offers.